2009
DOI: 10.1038/gt.2009.95
|View full text |Cite
|
Sign up to set email alerts
|

Systemic administration of a PEGylated adenovirus vector with a cancer-specific promoter is effective in a mouse model of metastasis

Abstract: Cancer gene therapy by adenovirus vectors (Advs) for metastatic cancer is limited because systemic administration of Adv produces low therapeutic effect and severe side effects. In this study, we generated a dual cancer-specific targeting vector system by using PEGylation and the telomere reverse transcriptase (TERT) promoter and attempted to treat experimental metastases through systemic administration of the vectors. We first optimized the molecular size of PEG and modification ratios used to create PEG-Ads.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 44 publications
0
80
0
Order By: Relevance
“…13,14) Furthermore, although still in the preclinical stage, PEGylated adenoviruses (PEG-Ad) have been developed and have shown higher accumulation rates, stronger tumor-suppressive activity, and fewer hepatotoxic side effects than unmodified adenoviruses (Ad). 10,[15][16][17][18] In contrast to the preceding argument, we and others have reported that PEGylated liposomes lose the expected long circulating property when they are injected repeatedly in the same animal (the so-called accelerated blood clearance (ABC) phenomenon). 19,20) On the basis of our earlier results, 21,22) we proposed the following tentative mechanism for the cause of this phenomenon: anti-PEG IgM, which is produced in the spleen in response to the initial dose, selectively binds to the PEG of the second dose liposomes injected several days later Regular Article * To whom correspondence should be addressed.…”
mentioning
confidence: 72%
See 3 more Smart Citations
“…13,14) Furthermore, although still in the preclinical stage, PEGylated adenoviruses (PEG-Ad) have been developed and have shown higher accumulation rates, stronger tumor-suppressive activity, and fewer hepatotoxic side effects than unmodified adenoviruses (Ad). 10,[15][16][17][18] In contrast to the preceding argument, we and others have reported that PEGylated liposomes lose the expected long circulating property when they are injected repeatedly in the same animal (the so-called accelerated blood clearance (ABC) phenomenon). 19,20) On the basis of our earlier results, 21,22) we proposed the following tentative mechanism for the cause of this phenomenon: anti-PEG IgM, which is produced in the spleen in response to the initial dose, selectively binds to the PEG of the second dose liposomes injected several days later Regular Article * To whom correspondence should be addressed.…”
mentioning
confidence: 72%
“…[15][16][17][18] In addition, they showed that the PEGylation to Ad can avoid production of specific neutralizing Abs to Ad following intravenous administration. 17) However, in the present study, we observed that a single intravenous injection of PEG-Ad elicits anti-PEG IgM, although neutralizing anti-Ad Abs were not detected (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4] These features make survivin of interest in targeted cancer therapy. 5 Gene therapy holds promise for the treatment of various diseases for which there is little hope of finding a conventional cure. 6 Cancer is the leading cause of death in economically developed countries, 7 and is a major public health problem throughout the world.…”
Section: Introductionmentioning
confidence: 99%